Cultural Value Differences, Value Stereotypes, and Diverging Identities in Intergroup Conflicts: The Estonian Example - Dobewall, Henrik; Strack, Micha (International Journal of Conflict and Violence (IJCV), 2011)
An examination of the relationship between cultural values, value stereotypes and social identities in Estonia, where intergroup conflicts triggered riots in the capital Tallinn in April 2007, using data from the European Social Survey on cultural differences and value trends as the background to a survey exploring perceived group values and assessed social identities among ethnic Estonians and members of the Russian-speaking minority. The study, conducted in summer 2008, found agreement across both ethnic groups about the values of a typical group member, but no accuracy in their attribution. The Estonian students (n = 152) avoided Eastern-European identification, while the Russian-speaking students (n = 54) did not want to give up Estonia’s Soviet past. We found that attributed rather than self-rated value differences between groups caused the conflicts, whilst diverging identities were found to make value stereotypes more extreme.